2010
DOI: 10.1186/1471-2164-11-709
|View full text |Cite
|
Sign up to set email alerts
|

Temporal transcriptomic response during arsenic stress in Herminiimonas arsenicoxydans

Abstract: BackgroundArsenic is present in numerous ecosystems and microorganisms have developed various mechanisms to live in such hostile environments. Herminiimonas arsenicoxydans, a bacterium isolated from arsenic contaminated sludge, has acquired remarkable capabilities to cope with arsenic. In particular our previous studies have suggested the existence of a temporal induction of arsenite oxidase, a key enzyme in arsenic metabolism, in the presence of As(III).ResultsMicroarrays were designed to compare gene transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 34 publications
6
64
0
1
Order By: Relevance
“…Arsenite early exposure (15 minutes) induced the transcription of two usp genes in Herminiimonas arsenicoxydans , a bacterium isolated from arsenic-contaminated sludge 40. A usp gene and an arsenic resistance operon are located on an antibiotic-resistant island in the genome of Acinetobacter baumannii , an opportunistic pathogen that causes nosocomial infections 41.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenite early exposure (15 minutes) induced the transcription of two usp genes in Herminiimonas arsenicoxydans , a bacterium isolated from arsenic-contaminated sludge 40. A usp gene and an arsenic resistance operon are located on an antibiotic-resistant island in the genome of Acinetobacter baumannii , an opportunistic pathogen that causes nosocomial infections 41.…”
Section: Discussionmentioning
confidence: 99%
“…It is not immediately apparent why, or how, such a transporter might be involved (or not) in As III oxidation or metabolism. Previously reported microarray studies also identified the As III induction of a C 4 -dicarboxylate transporter in H. arsenicoxydans (8). The Dct system in strain 5A is a secondary transporter operating without a periplasmic solute binding protein, whereas the As III -inducible dctPMQ dicarboxylate transporter in H. arsenicoxydans is annotated as a tripartite ATP-independent periplasmic (TRAP)-type transporter (reviewed in reference 45).…”
Section: Discussionmentioning
confidence: 99%
“…In comparative proteomic and genomic analyses in the pres- ence or absence of As(III), the enzymes involved in the tricarboxylic acid (TCA) cycle were upregulated after the addition of As(III), indicating the bacteria needed a large amount of energy to resist As(III) toxicity (140)(141)(142). In contrast, the TCA cycle in A. tumefaciens GW4 was downregulated by the addition of As(III).…”
Section: Metabolic Pathways Associated With Antimonite Resistancementioning
confidence: 99%